2023
DOI: 10.1002/smtd.202201344
|View full text |Cite
|
Sign up to set email alerts
|

Designing Low Tortuosity Electrodes through Pattern Optimization for Fast‐Charging

Abstract: The development of fast-charging technologies is crucial for expediting the progress and promotion of electric vehicles. In addition to innovative material exploration, reduction in the tortuosity of electrodes is a favored strategy to enhance the fast-charging capability of lithium-ion batteries by optimizing the ion-transfer kinetics. To realize the industrialization of low-tortuosity electrodes, a facile, cost-effective, highly controlled, and high-output continuous additive manufacturing roll-to-roll scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Because of its high surface area, excellent stability, and low cytotoxicity, zeolitic imidazolate framework-8 (ZIF-8) composed of Zn 2+ coordinated with 2-methylimidazole (2-mIM) is one of the most popular and well-studied MOF materials. 23–26 In this study, ZIF-8 was selected as the candidate MOF material, and the controlled co-precipitation strategy with polyvinylpyrrolidone (PVP) as the capping agent was adopted. 2,27 Of note, a low 2-mIM/Zn molar ratio of 8 : 1 was used to prepare the KmCR2@ZIF biocomposites, as previous studies indicated that biocomposites synthesized with a low 2-mIM/Zn molar ratio possessed higher enzyme loadings and specific activities than those fabricated with a high 2-mIM/Zn molar ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its high surface area, excellent stability, and low cytotoxicity, zeolitic imidazolate framework-8 (ZIF-8) composed of Zn 2+ coordinated with 2-methylimidazole (2-mIM) is one of the most popular and well-studied MOF materials. 23–26 In this study, ZIF-8 was selected as the candidate MOF material, and the controlled co-precipitation strategy with polyvinylpyrrolidone (PVP) as the capping agent was adopted. 2,27 Of note, a low 2-mIM/Zn molar ratio of 8 : 1 was used to prepare the KmCR2@ZIF biocomposites, as previous studies indicated that biocomposites synthesized with a low 2-mIM/Zn molar ratio possessed higher enzyme loadings and specific activities than those fabricated with a high 2-mIM/Zn molar ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, screen printing holds the advantage of faster printing than inkjet printing, which needs to sequentially define each pattern region. For even faster printing, a roll-to-roll (R2R) form of screen printing was demonstrated by employing highly efficient cylinder presses. , In contrast to flat-screen printing, the screen, cylinder, and substrate move synchronously, while the presses and squeegee remain stationary. The R2R process allows for high-throughput printing with operation speeds of up to 80 m 2 ·s –1 .…”
Section: Tmd Ink Formulation and Coating/printing Strategiesmentioning
confidence: 99%
“…Reproduced with permission. [ 202 ] Copyright 2023, Wiley VCH GmbH. b) Schematic design and fabrication of fiber‐aligned thick electrode followed by rolling into cylindrical shape electrode.…”
Section: Charge Storage Devicesmentioning
confidence: 99%